2020
DOI: 10.18510/hssr.2020.82e14
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Arabic Language Speaking Anxiety and Motivation Among Religious Secondary School Students in Malaysia

Abstract: Purpose of the study: This study aimed at identifying the level of Arabic language speaking anxiety and its relationship to motivation among students of religious secondary schools in Malaysia. Methodology: This quantitative study identifies the anxiety level in speaking Arabic and its relationship with motivation. A survey was done with a selected number of 500 Arabic students out of the total population throughout Malaysia. The survey was done using questionnaires that have been adapted and modified fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In other words, the higher the learner's anxiety, the lower the learner's WTC. Specifically, (Ismail et al, 2020) found that the aspect of anxiety when facing oral Arabic tests attained the highest mean among students, which shows that students often undergo speaking anxiety when facing oral Arabic tests. Thus, it is important to identify the factors of test anxiety in learning a foreign language which is emphasized by Aydin et al (2020) that the anxiety test also has certain influences on the foreign language learning process and achievement.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In other words, the higher the learner's anxiety, the lower the learner's WTC. Specifically, (Ismail et al, 2020) found that the aspect of anxiety when facing oral Arabic tests attained the highest mean among students, which shows that students often undergo speaking anxiety when facing oral Arabic tests. Thus, it is important to identify the factors of test anxiety in learning a foreign language which is emphasized by Aydin et al (2020) that the anxiety test also has certain influences on the foreign language learning process and achievement.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the teaching and learning of the Arabic Language in Malaysia, although most Malaysian learners have started to learn Arabic since primary school, they still try to avoid communicating in Arabic when asked to do so during Arabic lessons. According to Ismail et al (2020), even religious secondary school students were anxious and fearful of speaking Arabic as a second language, especially when facing oral tests, because they could not organize and present their speech correctly and confidently. Studies have shown that a high level of anxiety occurs mostly related to understanding and speaking the target language (Alghali, 2016).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Dubin (1977) also agrees that continuous motivation and language training is necessary to master a foreign language. Nevertheless, Ismail et al (2020) found that Arabic speaking anxiety faced by students does not have a significant relationship with motivation. As reported by (Hashimoto, 2002;Huang, 2005;Liu, 2011), the fear experienced by the students when speaking English does not significantly relate to motivation.…”
Section: Fear Of Oral Presentationmentioning
confidence: 88%
“…This is indicated that the spirit of religious study of students in rural areas is better. Students' motivation has a difference between urban and rural areas [26], [27]. Some influences that can influence this are students' internal and external factors.…”
Section: Motivation To Study Islamic Religious In Madrasah Ibtidaiyahmentioning
confidence: 99%